The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1093/ajcn/32.8.1679
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin C, vitamin B6, and vitamin B12 supplementation on the breast milk and maternal status of well-nourished women

Abstract: The effects of vitamin supplements and/or diet on the levels of vitamin C, vitamin B6, and vitamin B12 in milk and blood of lactating women were determined. At the end of gestation, subjects were divided into two lactation groups: supplemented (10 subjects) and nonsupplemented (seven subjects). Milk samples were collected from 5 to 7 days and 43 to 45 days postpartum. Fasting blood samples were drawn at 8 and 46 days postpartum for vitamin C, B6, and B12 status measurements. Dietary records of all foods consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 15 publications
5
22
0
Order By: Relevance
“…The mean concentration of ascorbic acid in maternal milk (Table 3) was similar to that reported in other studies (Fomon, 1974;Thomas et al 1979;Sneed et al 1981;Byerley & Kirksey, 1985;Schwartz, 1985). However, it was greater than that recorded in still others (Bates et al 1983(Bates et al , 1994Committee on Nutrition, 1985) (Table 4).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mean concentration of ascorbic acid in maternal milk (Table 3) was similar to that reported in other studies (Fomon, 1974;Thomas et al 1979;Sneed et al 1981;Byerley & Kirksey, 1985;Schwartz, 1985). However, it was greater than that recorded in still others (Bates et al 1983(Bates et al , 1994Committee on Nutrition, 1985) (Table 4).…”
Section: Discussionsupporting
confidence: 88%
“…Others have reported that when intake is low, breast milk ascorbic acid levels are sensitive to supplementation. However, when intake is high, breast milk levels are much less sensitive (Thomas et al 1979;Sneed et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing infants from multivitamin-supplemented mothers to infants from non-multivitamin-supplemented mothers, we found a major effect in serum vitamin B12 at 6 weeks that was sustained through 6 months of age. Observational studies had suggested that the vitamin B12 status of newborns is strongly associated with that of their mothers (Bjorke Monsen et al, 2001) and that correction of deficiencies through vitamin B12 supplementation among presumably HIV-uninfected mothers resulted in greater B12 concentrations in breast milk (Thomas et al, 1979(Thomas et al, , 1980Sneed et al, 1981). It has been described that vitamin B12 concentrations decrease in the newborn during the first 6-8 weeks (Bjorke Monsen & Ueland, 2003); our results suggest that maternal supplementation with multivitamins at multiples of the recommended dietary allowance (RDA) in USA could prevent such a decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies among presumably HIV-uninfected women have shown that supplementation with vitamins A and B12 during early lactation increases the concentrations of nutrients in breast milk and results in improved vitamin status of infants during the first 6 months (Thomas et al, 1979;Sneed et al, 1981;Stoltzfus et al, 1993;Roy et al, 1997;Muslimatun et al, 2001;Bahl et al, 2002). Therefore, it has been proposed that vitamin supplementation to lactating mothers may be an efficient way to improve the vitamin status of both mothers and infants (Stoltzfus et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…() 16 9 7 USA Mean ± SE (a) Supplementation with vitamin B6 (b) Total vitamin B6 intake Supplemented group 5–7 days post‐partum (a) 4 (b) 5.33 ± 0.29 (SE) 43–45 days post‐partum (a) 4 (b) 5.12 ± 0.31 (SE) Unsupplemented group 5–7 days post‐partum (a) 0 (b) 1.52 ± 0.40 (SE) 43–45 days post‐partum (a) 0 (b) 1.41 ± 0.56 (SE) 5–7 days post‐partum 43–45 days post‐partum 5–7 days post‐partum 43–45 days post‐partum Vitamin B6 Mean ± SD 248 ± 60 240 ± 57 123 ± 34 120 ± 33 Microbiological assay ( Saccharomyces uvarum ) 4‐day dietary records (from 4 to 7 days post‐partum and 42 to 45 days post‐partum) Multivitamin and mineral supplementation compared with no supplementation Expressed milk before taking supplementation or placebo No information on whether the infants were born at term or not Plasma PLP not assessed Styslinger and Kirksey () 24 6 6 6 6 USA Mean ± SEM: (a) Supplemental intake: four doses of PN‐HCl (b) Dietary vitamin B6 intake (c) Total vitamin B6 intake (a) 0 (b) 2.0 ± 0.1 (c) 2.0 ± 0.1 (a) 2.5 (b) 1.9 ± 0.1 (c) 4.4 ± 0.1 (a) 10.0 (b) 1.6 ± 0.1 (c) 11.3 ± 0.2 (a) 20.0 (b) 1.7 ± 0.5 (c) 21.1 ± 0.4 2–3 months post‐partum (mean stage of lactation: 11 weeks post‐partum) Vitamin B6 (Mean ± SEM) 93 ± 8 192 ± 16 247 ± 25 413 ± 45 Microbiological assay ( Saccharomyces uvarum ) Maternal intake estimated by a three‐day dietary record for 18 women, and a two‐day dietary record for three women Dietary records not available for three women Multivitamin and multimineral supplementation Supplementation was taken for three consecutive days Full‐term infants Plasma PLP concentration not assessed Thomas et al. () 17 10 7 USA Mean ± SE (a) Supplementation with vitamin B6 (b) Total vitamin B6 intake Supplemented group 5–7 days post‐partum (a) 4.0 (b) 5.69 ± 0.65 (SE) 43–45 days post‐partum (a) 4.0 (b) 5.11 ± 0.35 (SE) Unsupplemented group 5–7 days post‐partum (a) 0 (b) 1.45 ± 0.62 (SE) 43–45 days post‐partum (a) 0 (b) 0.84 ± 0.22 (SE) 5–7 days post‐partum 43–45 days post‐partum 5–7 days post‐partum 43–45 days post‐partum Vitamin B6 Mean ± SE 225 ± 87 237 ± 57 128 ± 59 204 ± 53 Microbiological assay ( Saccharomyces uvarum ) Four‐day dietary records (from 4 to 7 days post partum and 42 to 45 days post partum) Multivitamin and multimineral supplementation Milk collection: 3‐day periods at I and 6 weeks post partum Expressed milk before taking supplementation For the unsupplemented group, expressed milk bef...…”
Section: Appendix a – Concentrations Of Vitamin B6 In Breast Milk Of mentioning
confidence: 99%